2017
DOI: 10.1007/s00774-017-0887-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased calcium uptake and improved trabecular bone properties in intestinal alkaline phosphatase knockout mice

Abstract: Previous studies have demonstrated a negative correlation between intestinal alkaline phosphatase (IAP) activity and calcium (Ca) absorption in the gut, as IAP acts as a protective mechanism inhibiting high Ca entry into enterocytes, preventing Ca overload. Here we evaluated Ca absorption and bone properties in knockout mice (KO) completely devoid of duodenal IAP (Akp3 mice). Female C57BL/6 control mice (WT, n = 7) and KO mice (n = 10) were used to determine Ca absorption in vivo and by in situ isolated duoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…A study conducted in mice completely lacking duodenal IAP (Akp3−/−mice) showed mild atrophy of the villi with a lower absorption surface, resulting in higher calcium uptake than in the control mice. During long-term follow-up, mice lacking IAP had better bone properties than controls, providing evidence that IAP regulates calcium absorption [73].…”
Section: Transport Of Nutrients and Minerals Functionmentioning
confidence: 90%
“…A study conducted in mice completely lacking duodenal IAP (Akp3−/−mice) showed mild atrophy of the villi with a lower absorption surface, resulting in higher calcium uptake than in the control mice. During long-term follow-up, mice lacking IAP had better bone properties than controls, providing evidence that IAP regulates calcium absorption [73].…”
Section: Transport Of Nutrients and Minerals Functionmentioning
confidence: 90%
“…More recently, Brun et al showed that Akp3 -/-mice display higher intestinal Ca uptake and Ca retention [51]. Some previous reports indicate that high dietary Ca concentrations decrease Pi digestibility and absorption [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, accelerated transport of fat droplets through the intestinal epithelium and elevation of serum triglyceride levels were discernible, which was associated with higher intestinal Ca 2+ uptake. [22,23] Overexpression ALPP2…”
Section: Target Gene Outcome (Note) Referencementioning
confidence: 99%